2020
DOI: 10.1186/s12935-020-1106-5
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA ATXN7 promotes the development of gastric cancer through sponging miR-4319 and regulating ENTPD4

Abstract: Background: Circular RNAs (circRNAs) which are shown as a class of RNAs exhibit the importance in the regulation of gene expression and the development of biological process. However, the expression profile and molecular mechanism of circRNA ATXN7 (circATXN7) is still mostly uncertain in gastric cancer (GC). Methods: qRT-PCR analysis was performed to detect the expression of circATXN7, miR-4319 and ENTPD4 in GC tissues and cells. CCK-8, colony formation, EdU, flow cytometry, TUNEL and transwell assays were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 32 publications
3
19
0
Order By: Relevance
“…13 Here, we also showed miR-4319 was decreased expression in GC, and knockdown of miR-4319 stimulates GC cell growth, which is in consistent with the previous study result. 13 We also explored molecular mechanism by which KCNQ1OT1 regulates GC progression. We demonstrated KCNQ1OT1 interacts with miR-4319 to increase DRAM2 expression.…”
Section: Discussionsupporting
confidence: 92%
“…13 Here, we also showed miR-4319 was decreased expression in GC, and knockdown of miR-4319 stimulates GC cell growth, which is in consistent with the previous study result. 13 We also explored molecular mechanism by which KCNQ1OT1 regulates GC progression. We demonstrated KCNQ1OT1 interacts with miR-4319 to increase DRAM2 expression.…”
Section: Discussionsupporting
confidence: 92%
“…Fox instance, circ-HIPK3 was shown to be upregulated in human colorectal cancer and promoted tumorigenesis and progression via sponging miR-7 and increasing the levels a series of protooncogenes [13]. And circ-ATXN7 was significantly increased in gastric cancer and expedited tumor growth via absorbing miR-4319 and elevating ENTPD4 [14].…”
Section: Introductionmentioning
confidence: 99%
“…They can also act as templates for protein translation and mediate immune responses [ 7 , 8 ]. Dysregulation in their role as miRNA-sponge has been reported in several types of gastrointestinal malignancies, including hepatocellular carcinoma [ 9 , 10 , 11 ], pancreatic [ 10 , 12 ], colorectal [ 10 , 11 , 13 ] and gastric cancer [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ,…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies have demonstrated the role of circRNAs as miRNA-sponges in GC [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ]. For example, it has been shown that alterations in circLARP4/miR-424/LATS1 [ ...…”
Section: Introductionmentioning
confidence: 99%